2013
DOI: 10.1155/2013/398172
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Encephalopathy after Transjugular Intrahepatic Portosystemic Shunt in Patients with Recurrent Variceal Hemorrhage

Abstract: Purpose. The purpose of this study was to determine the incidence and predictors of hepatic encephalopathy (HE) after transjugular intrahepatic portosystemic shunt (TIPS) and endoscopic therapy (ET) in the elective treatment of recurrent variceal hemorrhage. Methods. Seventy patients were treated with elective TIPS and fifty-six patients with ET. Median observation time was 46.28 months in the TIPS group and 42.31 months in the ET group. Results. 30 patients (42.8%) developed clinically evident portosystemic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Reported incidence of post-TIPS HE has varied significantly across studies, ranging from 22% to 50% in individual series. 2,[12][13][14][15][16][17][18][19][20] In a meta-analysis of 14 randomized controlled trials which compared TIPS to standard therapy in variceal bleeding, the overall rate was found to be 33% in the TIPS group vs. 19% in the control group. 21 The definition of post-TIPS HE has also varied between studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reported incidence of post-TIPS HE has varied significantly across studies, ranging from 22% to 50% in individual series. 2,[12][13][14][15][16][17][18][19][20] In a meta-analysis of 14 randomized controlled trials which compared TIPS to standard therapy in variceal bleeding, the overall rate was found to be 33% in the TIPS group vs. 19% in the control group. 21 The definition of post-TIPS HE has also varied between studies.…”
Section: Discussionmentioning
confidence: 99%
“…11 Estimates range from 22% to 50% depending on the exact definition of HE used and patient demographics. 2,[12][13][14][15][16][17][18][19][20] Likewise, risk factors for development of post-TIPS HE have varied between studies. One large meta-analysis found age over 65, advanced Child-Pugh score and history of HE to be robust predictors.…”
mentioning
confidence: 99%
“…Merola et al showed that higher MELD scores, hyponatremia, and higher total bilirubin level were associated with the development of overt HE post-TIPS [18]. Other studies demonstrated that the risk of post-TIPS HE was higher in the patients with increased age, preexisting HE, and higher Child-Pugh score [19, 20]. Although there have been some hypotheses of HE, the underlying molecular mechanisms remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Also increased number of toxins are presented to liver hepatocytes for detoxification. This can be achieved by shunt reduction or occlusion techniques (6,7,19,21,30,36). An understanding of the anatomy and physiology of the portal system as well as porto-systemic haemodynamic and flow directional changes that occur in the presence of cirrhosis is essential prior to the discussion of techniques for shunt reduction.…”
Section: Endovascular Techniques Of Shunt Reductionmentioning
confidence: 99%
“…Hepatic encephalopathy is classified into three major categories, according to the underlying aetiology. Type A occurs in patients with acute liver failure, type B occurs in patients with portosystemic shunting without intrinsic liver disease and type C is related to cirrhosis .…”
Section: Introductionmentioning
confidence: 99%